La España Marítima (1838-1841), the first Spanish marine journal - Ibáñez, Itsaso; Fernández-Martínez, Luis-María (Revista General de Información y Documentación, 2018)
Periodicals are the main communication vehicle of scientific and professional communities. The process of specialization of scientific periodicals took place throughout the nineteenth century, although in Spain its consolidation did not occur until the twentieth century, due to the precarious scientific institutionalization the country suffered as a consequence of the political instability. Nevertheless, numerous specialized journals were edited during this difficult period, fact that is explained by the short life spans of most of these publications. The study of these journals has proved to be an effective means of tracking the diffusion of new ideas, hence their importance for the history of science and technology and the unquestionable interest of historical researchers in examining these printed sources. This article studies the first marine magazine, La España Marítima, published in Madrid, between 1838 and 1841, from the thorough analysis of the unique complete collection preserved, located in a private library. The study also allows to discuss the scientific relevance of this first journal as well as its effectiveness as a means of spreading scientific knowledge.